Using Mobile Gaming in Virtual Physical Education - Paolo Nino Valdez; Janet Mariano; Ma. Socorro Gigi Cordova (SOTL in the South)
Recent research in education during the COVID-19 pandemic has revealed several structural inequalities leading to problematic implementation of teaching and learning programs globally. However, while the use of communication technology has been greatly capitalized to bridge the physical distance between teachers and students, certain subjects such as Physical Education (henceforth PE) poses logistical challenges in terms of implementation since it entails actual development of physical skills on the part of the learner. This reflective piece examined the use of mobile gaming as an alternative to traditional Physical education programs. Specifically, we argue that mobile gaming helps develop  peer engagement, critical thinking, and communication skills. On the other hand, challenges such as a need to engage in more physical activities, addiction and access to technology were encountered.